Identifikasi Faktor-Faktor Perencanaan Permintaan Dan Penjualan Di PT. Tigaraksa Satria, Tbk. - , Robertus Himawan Indarto, Ir. Adhi Djoko Guritno, M.SIE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The current situation of business competition requires each company to provide high service distributor to each customer in order to create customer satisfaction. Services are provided in the amount of product, time and exact location to the customer. By considering the abovementioned things, this study aims to identify the factors that influence demand and sale of infant milk products. Knowing the demand for infant milk products as much and as early as possible, will provide a good overview for the product preparation This research was carried out by observing the processes of selling baby milk products which were applied by the PT. Tigaraksa Satria, Tbk. and focused on the development process of forecasting demand The results showed that when forecasting demand, there are factors that do affect the demand and the factors contained in the sales process that occurs over time. By identifying these factors, the process of forecasting demand will be getting better compared to nowadays